Strategic Role of the Petronas Twin Towers in Strengthening Malaysia’s International Tourism Image - M. Fhadil Alfharizi; Syafri Anwar; Dedi Hermon; Febriandi (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study aims to evaluate the strategic role of the Petronas Twin Towers as an international tourism symbol of Malaysia by analyzing their contribution to nation branding and competitiveness in the face of global competition dynamics. The research method used is descriptive qualitative with a single case study approach, utilizing primary data from field observations and secondary data from corporate reports. Data analysis was conducted using a SWOT analysis integrated with Internal Factors Analysis Summary (IFAS) and External Factors Analysis Summary (EFAS) matrices to determine the strategic position of the destination. The results indicate that the Petronas Twin Towers possess a strong competitive advantage, with internal strengths (score 2.25) outweighing weaknesses (score 1.60) and external opportunities (score 1.97) exceeding threats (score 1.45). The strategic analysis places the destination in Quadrant I (Aggressive Strategy), driven by its status as a global visual icon and the successful implementation of the Green Building Index (GBI) Gold certification. Consequently, the study recommends an aggressive growth strategy focused on strengthening brand equity to capture new markets specifically Middle Eastern and Gen-Z travelers and developing "Eco-Edutourism" programs that leverage the building’s sustainability features.